Біоморфологічні та популяційно-онтогенетичні маркери репродуктивної стратегії Carex bohemica Schreb. в умовах ex situ та in situ - Scherbakova, O.; Novosad, K.; Novosad, V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Objective – to analyse of biomorphological and populational ontogenetic characteristics of Carex bohemica Schreb. which defining the rreproductive strategy of the species. Material and methods. C. bohemica Schreb. – stenotypic hydrophilic, relict, rare species, is characterized by a disjunctive area (within Ukraine is represented by a small number of localities), an unstable population structure. The subject of the study is biomorphological characteristics (signs of life form, seasonal rhythmicity of sprout formation, the structure of monocarpic peduncles and seeds, the ability to vegetative reproduction, the efficiency of seed reproduction, etc.) and populationontogenetic characteristics (polyvariability of ontogenesis, rotational speed of generative generations, success of reproduction of populations etc.). Inspection of the species in situ was carried out on the territory of nature reserves (Slavutsky district, Khmelnitsky region) from 2009 to 2016. Under ex situ conditions the species was grown in containers under indoor conditions or on cultivation areas within the Kyiv region (Baryshevsky district). The work takes into account the modern level of plant biomorphology and uses the generally accepted populationontogenetic methods of research. Results. An analysis of the biomorphological and populationontogenetic characteristics of C. bohemica that determine the rreproductive species strategy is made. Conclusions. At the level of the organism the reproductive strategy of C. bohemica determining its reproductive strategy, priority is given to the continuous seasonal production of a large number of flowering shoots. Significant seed formation percentages of in situ and ex situ determine high levels of actual seed productivity. Among populational ontogenetic characteristics the rreproductive strategy of C. bohemica is defined by: the rapid pace of degenerative development and the rapid overturn of generative generations; the possibility of forming a powerful soil seed bank; high levels of seed similarity and rapid development of stairs; the possibility of replenishing the population with new generations of individuals throug hout the growing season; stretched flowering periods of populations.